The disclosure of shariah non-compliance (SNC) events by Islamic banks in Malaysia / Marina Mohamed and Norhazlina Ibrahim - Mohamed, Marina; Ibrahim, Norhazlina (Universiti Teknologi MARA Selangor, 2023)
Ensuring Shariah compliance in their business activities, products and services is paramount for Islamic Financial Institutions (IFIs) to preserve public confidence. However, the occurrence of occasional Shariah noncompliance (SNC) incidents is unavoidable, and these are triggered for various reasons. Thus, IFIs must ensure appropriate communication and disclosure regarding the occurrence of SNC events; the purification of SNC income; and the adoption of control measures for financial information users. Despite the importance of SNC disclosure, few studies have analysed in detail the disclosure of SNC events. Thus, this study aimed to investigate SNC events disclosure in detail for all 16 Islamic banks in Malaysia from 2015 to 2020. While all the Islamic commercial banks in Malaysia were found to disclose and report SNC occurrences in their annual reports, complete compliance with BNM requirements had yet to be reached. Several banks were found to have made commendable efforts to make useful information available, such as root causes, linked Islamic contracts and the tracking of SNC income disposal. However, fewer banks disclosed information on the nature of SNC events, rectification activities and the control measures taken in response to these events. Continuous monitoring and strong enforcement by the regulator are required to ensure that SNC events disclosure can be streamlined across all banks. These findings add value to the information users by assuring them of the Islamic banks' accountability in terms of transparency, as well as their effectiveness in managing and mitigating SNC events.